Analisis Pengaruh Ability, Effort Dan Support Terhadap Kinerja Karyawan Toko Buku Gramedia Cabang Plaza Semanggi - Puspokusumo, R. A. R. A. Aryanti Wardaya; Cathleen, Leonny (Binus Business Review, 2011)
The purpose of the article is to analyze the influence of ability, effort and support towards employee performance in Plaza Semanggi branch of Gramedia bookstore. Method used in this research is the correlation of Pearsonâs product-moment and double regression. The gathered data from questionnaire result provided uses likert scale and primary data from the company. The research result is to identify employeesâ ability, effort, and support of organization having strong relationship and significant influence towards employeesâ performance in Plaza Semanggi branchâs Gramedia bookstore. Hopefully, the organizationâs ability, effort and support could be increased and became main factor in increasing employeesâ performance. Besides, it is expected that the research result could give input for the company, especially in Plaza Semanggi branch, to increase the employeeâs performance, which later will give positive impact for company development.Â